Accelerating forward genetics for cell wall deconstruction - Vidaurre, Danielle; Bonetta, Dario (Frontiers in Plant Science, 2012)
One of the biggest challenges of cell wall biology is the elucidation of the genes involved the cell wall and their function due to the recalcitrance of the cell wall. Through traditional genetic approaches, many simple yet elegant screens have been able to identify components of the cell wall and their networks. Despite progress in the identification of several genes of the cell wall, there remain many unknown players whose function has yet to be determined. Exhausting the genetic toolbox by performing secondary screens on a genetically mutated background, chemical genetics using small molecules and improved cell wall imaging hold promise for new gene discovery and function. With the recent introduction of next-generation sequencing technologies, it is now possible to quickly and efficiently map and clone genes of interest in Arabidopsis and any model organism with a completed genome sequence. The combination of a classical genetics approach and cutting edge technology will propel cell wall biology of Arabidopsis and other useful crops forward into the future.